Determinants of Bone Material Strength and Cortical Porosity in Patients with Type 2 Diabetes Mellitus - Samakkarnthai, Parinya; Sfeir, Jad G; Atkinson, Elizabeth J; Achenbach, Sara J; Wennberg, Paul W; Dyck, Peter J; Tweed, Amanda J; Volkman, Tammie L; Amin, Shreyasee; Farr, Joshua N; Vella, Adrian; Drake, Matthew T; et al. (The journal of clinical endocrinology and metabolism, 2020)
Abstract Context Reduced bone material strength index (BMSi) and increased cortical porosity (CtPo) have emerged as potentially contributing to fracture risk in type 2 diabetes mellitus (T2DM) patients. Objective To determine whether BMSi or CtPo are related to other diabetic complications. Design Cross-sectional observational study. Setting Subjects recruited from a random sample of southeast Minnesota residents. Participants A total of 171 T2DM patients (mean age, 68.8 years) and 108 age-matched nondiabetic controls (mean age, 67.3 years). Main Measures Bone material strength index was measured using microindentation, skin advanced glycation end-products (AGEs) measured using autofluorescence, high-resolution peripheral quantitative computed tomography at the distal radius and tibia, assessment of diabetic microvascular complications including urine microalbuminuria, retinopathy, neuropathy, and vascular disease (ankle brachial index and transcutaneous oxygen tension [TcPO2]). All analyses were adjusted for age, sex, and body mass index. Results Skin AGEs were negatively correlated with the BMSi in both T2DM (r = -0.30, P < 0.001) and control (r = -0.23, P = 0.020) subjects. In relating diabetic complications to CtPo, we found that T2DM patients with clinically significant peripheral vascular disease (TcPO2 ≤ 40 mm Hg) had higher (+21.0%, P = 0.031) CtPo at the distal tibia as compared to controls; in these subjects, CtPo was negatively correlated with TcPO2 at both the distal tibia (r = -0.39, P = 0.041) and radius (r = -0.41, P = 0.029). Conclusions Our findings demonstrate that bone material properties are related to AGE accumulation regardless of diabetes status, while CtPo in T2DM patients is linked to TcPO2, a measure of microvascular blood flow.